Developing Archetypal Machines for a Sequence of Food-slurry processing operations: an overview (2011)
"The importance of cereal gruel as a highly nutritious food for infants in many countries in Africa cannot be overstated. Conventional methods of producing The importance of cereal gruel as a highly nutritious food for infants in many countries in Africa cannot be overstated. Conventional methods of producing these food-slurries prior to their consumption as food cannot meet up with the high demand for these gruels This current work is targeted at developing various archetypal machines for the improvement of the production of these food slurries. Three prototype machines have been developed and discussed in this paper, namely, the suction sieving machine, the vibration sieving machine and the continuous flow multi-stage milling machine. The results of performance analyses on these archetypal machines are presented and compared to ascertain their efficiencies and their appropriateness for different operations respectively. The results show that the machines have increased the sieving rate of steeped grain and in extension the production of these food-slurries by over 50%. Design considerations for a dual processing machine-assembly that combines the sieving and milling processes into a single operation is herein presented as the focus for future works. Conclusively, this work presents a remarkable contribution to research on the improvement of the production of various cereals gruels in Nigeria and many developing nations through the introduction of new processing technologies. "